Development of total quality intellection in libraries in order to improve user satisfaction - Bayter, Mustafa (Qualitative and Quantitative Methods in Libraries; Vol 7 No 1 (2018): March 2018 Issue, 2019)
Total quality management can be defined as “ Focusing quality in an organization, depending on participation of all members of organization, purposing long term success by user satisfaction and a management approach provides benefit to society and all members of organization”. According to the libraries; A management mode aims to increase society and user satisfaction by active participation of labours and always improves all activation of a library. Based to execute anticipation of internal and external users aims to manage well all service activity processes. The existence of libraries, user satisfaction and for this to be provided given value to the stuff, moderate approach; constitutes importance in sight of community development. . Responses to what users ask for: Special interest superior quality, convenience, innovation, good presentation, richness and reliability in services. Unconditional user satisfaction and priority are the right user and right time to lock the stereotypical words like user. In order to improve the total quality management approach in libraries, the importance, benefits, solutions, and recommendations in total quality management will be included in the libraries. In addition, the questions about how users can be satisfied with total quality management will be replied. In order to be able to configure the services, the description of the study will be used because the users at the central point and the library staff who provide the service are asked to learn how the total quality management understanding has recently changed and developed with each other.